A GIS Procedure to Assess Shoreline Changes over Time Using Multi-temporal Maps: An Analysis of a Sandy Shoreline in Southern Italy over the Last 100 Years - Pepe, Massimiliano; Costantino, Domenica; Alfio, Vincenzo Saverio (Geomatics and Environmental Engineering, 2023)
The aim of the paper is to identify a methodology capable of assessing shoreline changes through a geomatic approach based on the use of GIS (Geographic Information System) software. The paper describes a case study that reports the evolution of a coastline over a period of more than 100 years using medium and large-scale metric maps available in different periods. In fact, the coastlines were obtained from the source maps of the Italian Cadastre (dated 1890), from numerical cartography available on the coastline and acquired in different period at scales 1:5000 and 1:2000 and, more recently, from the Google Earth Pro platform. To analyse the evolution of the coastline a new procedure has been performed which is based on the use of GIS software, in particular a plugin called DSAS that allows the evaluation of the changes in the coastline and also obtains a statistical analysis of its evolution. The results showed the ease and applicability of the method in determining the evolution of the coastline and the strong erosion of a stretch of coastline with important socio-economic consequences and repercussions was highlighted in the analysed case study.